Active-modulated, random-illumination, super-resolution optical fluctuation imaging. Issue 32 (7th August 2020) - Wang, Baoju; Liu, Zhijia; Zhou, Li; Fei, Yiyan; Yang, Chengliang; Mi, Lan; Mu, Quanquan; Ma, Jiong
Abstract : Super-resolution optical fluctuation imaging (SOFI) provides subdiffraction resolution based on the analysis of temporal stochastic intensity fluctuations. Abstract : Super-resolution optical fluctuation imaging (SOFI) provides subdiffraction resolution based on the analysis of temporal stochastic intensity fluctuations. However, conventional SOFI imaging relies on the intrinsic blinking properties of fluorescent markers and suffers from severe artifacts and signal losses owing to the unmatched blinking on-time ratio. Herein, we propose active-modulated, random-illumination, super-resolution optical fluctuation imaging that allows the traditional SOFI to overcome the effect of the intrinsic impertinent blinking characteristic of fluorescent markers. We demonstrate theoretically and experimentally that this method of active-modulated random illumination can generate random illumination patterns with a controllable blinking on-time ratio to match the high-order SOFI reconstruction considerably reducing the generated artifacts and signal losses. High-order, high-quality images can be obtained with increased lateral resolution.